THE ASSOCIATIONS BETWEEN HANDGRIP STRENGTH AND ITS CHANGE ON CARDIOVASCULAR INCIDENCE - Prasitsiriphon, O. (Innov Aging, 2017)
Handgrip strength (HGS) is increasingly becoming a vital factor in physical capability. The last decade has seen a renewed importance in the association between HGS and diabetes, hypertension, and cardiovascular mortality rather than disability and mortality. As far as I known it is not yet known whether the HGS and its change associated with cardiovascular incidence among older adults in European countries. Data are drawn from the first four waves of the Survey of Health, Ageing and Retirement in Europe (SHARE) with information on HGS, health and demographic characteristics from 7,232 participants aged 50–79 across 10 European countries. HGS was transformed as the low HGS (LGS), the fastest decline in HGS (FDGS), and the combination of the LGS and the FDGS (CBGS). Logistic regression models adjusted for the potential confounders showed that the FDGS and the CBGS were significantly correlated with cardiovascular incidence. However, the LGS as the lowest quintile HGS at baseline Wave was not significantly different from the normal HGS (NGS) on cardiovascular incidence. Both sexes with FDGS would have higher odds of experiencing cardiovascular development (all, P<0.02). In the CBGS, men with NGS&FDGS (P=0.008) and women with LGS&FDGS (P=0.000) were likely to have higher odds of having cardiovascular diseases. In conclusion, the decline in HGS and the CBGS should be considered as an indicator of incidence of cardiovascular disease among older adults. The further studies on the current topic are therefore suggested in order to establish in clinical setting.